Book Reviews - Richard Gore; Jennifer Harrison; Tamara Lavrencic; Colleen Pritchard; Anne-Marie Schwirtlich; Susan Healy; Baiba Berzins; Judy Seeff; Ian Pearce; Tony Marshall; Sigrid McCausland (Archives & Manuscripts, 1989)
Relations in records reviewed by Richard Gore p. 69-70; Relations in records reviewed by Jennifer Harrison p. 70-73; Glossary of basic conservation terms reviewed by Tamara Lavrencic p. 73-74; The management of business records reviewed by Colleen Pritchard p. 75-77; Directory of Irish archives reviewed by Anne-Marie Schwirtlich p. 77-79; Bound for Australia reviewed by Susan Healy p. 79-80; Conference papers: off the beaten track reviewed by Baiba Berzins p. 80-82; Archive of Australian judaica reviewed by Judy Seeff p. 82-84; Investigating the value of Commonwealth records reviewed by Ian Pearce p. 84-85; Treasures of the State Library of New South Wales reviewed by Tony Marshall p. 85-87; A source of inspiration and delight reviewed by Sigrid McCausland p. 87-90